Policy Analysis, Formulation of Strategic Plan Policy Implementation (Renstra) In Pandeglang Regency - Taufiqurokhman Taufiqurokhman (Universitas Prof. Dr. Moestopo (Beragama), 2019)
Important factors in the analysis of the formulation of the Strategic Plan (Renstra) policy implementation are community participation and decentralization. Namely, community involvement in the policy formulation process and the transfer of authority from the central government to autonomous regions in determining and implementing policies, through local voice and local choices.The research objectives, looking at the level of community participation and handing over of authority, have implications for the making of regional strategic plans, in identifying needs and formulating development goals.The research method used qualitative, through a descriptive approach, namely collecting data from various sources, with triangulation techniques. The research objectives, describe three things, (1) agenda setting, policy formulation, (2) budgeting in a participatory formulation; (3) development planning stakeholders.The results showed that participation in development planning at the tokenism and representative-elitist stages, the partnership between the community and the bureaucracy and political officials was a subordinate union of partnership, while the dialogue being held was still artificial.